Target yield based integrated nutrient management in rice (Oryza sativa)-wheat (Triticum aestivum) cropping system - SINGH, JAGDEEP; MAVI, M S; SAINI, SAT PAL (The Indian Journal of Agricultural Sciences, 2021)
Target yield equation-based integrated nutrient management studies were conducted to examine its importance in attaining target yields, improving soil nutrient status, and nutrient utilization in rice (Oryza sativa L.)-wheat (Triticum aestivum L.) cropping sequence. The study was carried out for three years in the rice-wheat cropping system. The nitrogen (N), phosphorus (P), and potassium (K) requirement for attaining target yield of 7.5 t/ha for rice and 5 t/ha of wheat were estimated following soil test crop response-based target yield equations (TYE). The treatments consist of differential fertilization as the chemical source and farmyard manure (FYM) as the organic source. Results indicated that 97.2% of the target in rice and 94% in wheat, with negligible deviance from the quantified target yield, were achieved. Integrated nutrient management (INM) produced a significantly higher yield of rice (7.29 t/ha) and wheat (4.70 t/ha) when 100% INM was compensated with 75% fertilizer NPK and 25% organic N. The system productivity of 12.4 t/ha was the highest based on rice and rice equivalent yield of wheat in 100% INM. Likewise, nutrient uptake and nutrient productivity were also higher in crops with 100% INM. Moreover, the improved nutrient status and soil nutrient balance were more prominent with 100% INM. Therefore, the results demonstrated the beneficial effects of TYE-INM in the rice-wheat cropping system to obtain higher grain yields while maintaining soil health.